2007
DOI: 10.1186/1471-2458-7-171
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for low back pain among professional cooks working in school lunch services

Abstract: Background: The prevalence of self-reported low back pain among professional cooks was estimated to examine the effects of daily life conditions, job-related factors, and psychological factors on this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 33 publications
7
47
4
Order By: Relevance
“…A 12 month prevalence was high among homemakers (77%), comparable to a cohort of saleswomen in Thailand, who reported 77% prevalence, and 73% among professional cooks in Japan. However, the prevalence was higher than that found among office workers in Thailand (63%) and elementary school teachers in Brazil (55%) and an adult female population in Japan (42%) (Suka and Yoshida 2005, Nagasu et al 2007, Janwantanakul et al 2008, Cardoso et al 2009, Pensri et al 2009). This high prevalence suggests that it would be worthwhile to examine whether housework is an independent risk factor contributing to the development of MS disorders among women.…”
Section: Resultsmentioning
confidence: 69%
“…A 12 month prevalence was high among homemakers (77%), comparable to a cohort of saleswomen in Thailand, who reported 77% prevalence, and 73% among professional cooks in Japan. However, the prevalence was higher than that found among office workers in Thailand (63%) and elementary school teachers in Brazil (55%) and an adult female population in Japan (42%) (Suka and Yoshida 2005, Nagasu et al 2007, Janwantanakul et al 2008, Cardoso et al 2009, Pensri et al 2009). This high prevalence suggests that it would be worthwhile to examine whether housework is an independent risk factor contributing to the development of MS disorders among women.…”
Section: Resultsmentioning
confidence: 69%
“…In addition to burn and cut injuries, low back pain (LBP) is prevalent in these working populations found in previous studies [5][6][7][8] . LBP is the most frequent cause of disability compensation, accounting for a very large portion of workers' compensation cost in industrialized countries [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Shorter length of employment (<1 yr 23) , ≤5 yr 18,19,21) ) and overtime work schedules, which include working at least 12 h per day or 60 h per wk 24,25) , have been reported to be risk factors as well as night and evening shifts 16,25) . In addition to these studies, a cross-country questionnaire survey on risk factors for LBP among Japanese school lunch cooks showed that the height of cooking equipment, inadequate for the body height of a worker, and the number of cooked lunches per cook (≥150 meals) was associated with LBP 8) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low back pain (LBP) is a common health problem across all age groups [1][2][3] . Generally females and older people report more LBP 4,5 , whereas older adults have a higher risk of frequency LBP compared with young adults 6 .…”
Section: Introductionmentioning
confidence: 99%